Solid Substrate Fermentation of Cassava Pellets Using Tempeh Mould (Rhizopus oligosporus ) and Soya Sauce Mould (Aspergilus Oryzae) - A. Basrah Enie; Saib Alaban Hasibuan (Warta Industri Hasil Pertanian, 1986)
Cassava pellets were fermented for 1, 2, 3, and 4 days at room temperature using tempeh mould (Rhizopus oligosporus) and soya sauce mould (Aspargillus oryzae). After 2 days fermentation, the protein content of products were slightly increased from 1.29% (unfermented) to 1.52% (fermented by Rhizopus oligosporus) and to 1.58% (fermented by Aspergillus oryzae), however after 3 days fermentation the protein content tend to decrese. The pH of products drop after 2 days fermentation from 6.39 to 4.42 (R.oligosporus) and to 5.62 (A. oryzae). Organoleptic test showed that the acceptability of products were decreased after one day fermentation (taste and flavor) and after two days fermentation (colour).